PENINGKATAN PENGETAHUAN MENGHAPAL SURAH PENDEK AL QUR’AN MELALUI METODE READING ALOUD DI SEKOLAH DASAR - Sulaiman Sulaiman (Universitas Tanjungpura, 2022)
Selection The object of class action research is based on the fact that the students' knowledge ability in recognizing memorizing the Qur'an in short surah is still very low. This research was conducted in January-May 2015, because in those months students had completed the general semester exam and were still at the beginning of the semester so that the students' conditions could be observed from the beginning. Reading aloud method (hard reading) is a very appropriate learning method to get overall and individual class participation. This method provides an opportunity for each student to come forward memorizing the Qur'an in short surah. With thistechnique, students who have not wanted to advance to come forward memorizing the Qur'an in learning will be motivated to appear actively. From this study it can be concluded that with the existence of motivation in the learning method of reading aloud this, the learning outcomes will beoptimal. The more precise the motivation given, the more successful the lesson will be. With high motivation, student learning efforts will be high too. So motivation will always determine the intensity of student learning. This will improve student learning achievement.